Microsoft Internet Explorer 4.0 - O'Leary, Timothy J. (Irwin McGraw-Hill, 1999)
This beginner's guide provides students with a complete look at the Web using Internet Explorer 4.0. The easy-to-follow, highly visual approach introduces helpful tips and resources related to Internet usage while incorporating the new and enhanced features of the latest version of Microsoft's Internet browser (I. E. 4.0).